EDUCATIONAL VALUES IN RAYA AND THE LAST DRAGON: A CHARACTER EDUCATION APPROACH TO TEACHING ENGLISH - Mafaza Nabila; Senowarsito Senowarsito; Arso Setyaji (LEAD (Language, Education and Development), 2025)
The aims of the study are to analyze the educational values contained in the film Raya and the Last Dragon and their relevance to character education in English language learning for children. This study uses John Dewey's theory of educational values as the main framework, which is linked to Thomas Lickona's theory of character education. The method employed in this study is a descriptive, qualitative approach that utilizes documentary analysis techniques. Data was collected from dialogues, narratives, and scenes in the film. The researcher analyzed data containing educational values, as outlined by John Dewey (1994), and then categorized these values into four groups: moral, social, intellectual, and aesthetic values. The analysis results indicate that the film contains various educational values, with the following results: moral values (32.06%), social values (26.67%), intellectual values (24.76%), and aesthetic values (16.51%). Of all these educational values, there is a significant relationship with Thomas Lickona's (1996) theory of character education, which divides character values into five main points: caring, fairness, responsibility, respect, and honesty. These educational values are presented both explicitly and implicitly through characters, conflicts, and problem-solving in films. Based on the results of this research, it is hoped that animated films can contribute to English teachers, especially in teaching character values contextually and attractively to students through an English learning approach at the elementary school level.